Quantifying soil organic carbon after biochar application: how to avoid (the risk of) counting CDR twice? - Rathnayake, Dilani; Schmidt, Hans-Peter; Leifeld, Jens; Bürge, Diane; Bucheli, Thomas D.; Hagemann, Nikolas (Frontiers in Climate, 2024)
Pyrogenic carbon capture and storage (PyCCS), which comprises the production of biomass, its pyrolysis, and the non-oxidative use of the biochar to create carbon sinks, has been identified as a promising negative emission technology with co-benefits by improving soil properties. Using biochar as a soil additive becomes increasingly common as farmers seek methods for soil improvement and climate change adaptation. Concurrently, there is growing interest in quantifying soil organic carbon (SOC) at the level of individual plots to remunerate farmers for their good agricultural practices and the resulting (temporary) carbon dioxide removal (CDR). However, methods currently applied in routine analysis quantify SOC irrespective of its speciation or origin and do not allow to distinguish biochar-C from SOC. As certification of PyCCS-derived CDR is already established using another quantification method (i.e., analysis of biochar-C content, tracking and registration of its application, offsetting of carbon expenditures caused by the PyCCS process), the analysis of biochar-C as part of SOC may result in double counting of CDR. Hence, the objectives of this review were (1) to compare the physicochemical properties and the quantities of biochar and SOC fractions on a global and field/site-specific scale, (2) to evaluate the established methods of SOC and pyrogenic carbon (PyC) quantification with regard to their suitability in routine analysis, and (3) to assess whether double counting of SOC and biochar C-sinks can be avoided via analytical techniques. The methods that were found to have the potential to distinguish between non-pyrogenic and PyC in soil are either not fit for routine analysis or require calibration for different soil types, which is extremely laborious and yet to be established at scale. Moreover, the omnipresence of non-biochar PyC in soils (i.e., from forest fires or soot) that is indistinguishable from biochar-C is an additional challenge that can hardly be solved analytically. This review highlights the risks and limits of only result-based schemes for SOC certification relying on soil sampling and analysis. Carbon sink registers that unite the (spatial) data of biochar application and other forms of land-based CDR are suggested to track biochar applications and to effectively avoid double-counting.